Nomenklatorische Notizen zu Cicindela (Coleoptera). - Schilder, Franz Alfred (Contributions to Entomology = Beiträge zur Entomologie, 1953)
Nomenclatural Acts gigantula Schilder, 1953 (Cicindela), nom. n. pro Cicindela gigantea Raffray, 1885, nec Thunberg, 1781 ornatipennis Schilder, 1953 (Cicindela), nom. n. pro Cicindela ornata Fleutiaux, 1898, nec Klug, 1834 viridipennis Schilder, 1953 (Cicindela), nom. n. pro Cicindela viridis Raffray, 1882, nec Dejean, 1831 horni Schilder, 1953 (Odontochila), nom. n. pro Odontochila angustata Dejean, 1825, nec Fischer, 1824